Fighting on two fronts: Elevated insect resistance in flooded maize. (22nd August 2019) - Block, Anna K.; Hunter, Charles T.; Sattler, Scott E.; Rering, Caitlin; McDonald, Samantha; Basset, Gilles J.; Christensen, Shawn A.
Abstract: To grow and thrive plants must be able to adapt to both adverse environmental conditions and attack by a variety of pests. Elucidating the sophisticated mechanisms plants have developed to achieve this has been the focus of many studies. What is less well understood is how plants respond when faced with multiple stressors simultaneously. In this study, we assess the response of Zea mays (maize) to the combinatorial stress of flooding and infestation with the insect pest Spodoptera frugiperda (fall armyworm). This combined stress leads to elevated production of the defence hormone salicylic acid, which does not occur in the individual stresses, and the resultant salicylic acid‐dependent increase in S. frugiperda resistance. Remodelling of phenylpropanoid pathways also occurs in response to this combinatorial stress leading to increased production of the anti‐insect C‐glycosyl flavones (maysins) and the herbivore‐induced volatile phenolics, benzyl acetate, and phenethyl acetate. Furthermore, changes in cellular redox status also occur, as indicated by reductions in peroxidase and polyphenol oxidase activity. These data suggest that metabolite changes important for flooding tolerance and anti‐insect defence may act both additively and synergistically to provide extra protection to the plant. Abstract : Flooding stress in Zea mays leads to a salicylic acid‐dependent increase in resistance to the insect pest Spodoptera frugiperda . This combinatorial stress results in phenylpropanoid remodelling, changes in maysin and herbivore‐induced volatile production, and altered cellular redox status.